FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN M-BANKING BAGI MAHASISWA EKONOMI SYARIAH UNTIRTA - Aulia, Muhamad Akbar; Savira, Zelda Salma; Fajrin, Nabila; Marlina, Ina; Umam, Ahmad Khotibul (Diponegoro Journal of Islamic Economics and Business, 2024)
This research examines the factors influencing the decision to use m-banking for UNTIRTA Sharia economics students. This quantitative research uses multiple linear regression analysis. The population in this study were all UNTIRTA Sharia economics students. The data is primary data using a questionnaire and distributed as many as 101 results. The sampling technique is to use the lameshow formula. This research is quantitative research with data analysis methods using multiple linear regression. The results of this research state that there is a positive influence between the quality of trust on the decisions of Islamic economics students as proven by the results of the partial correlation test which shows a significance of 0.002<0.050 and a t value of 3,231>0.134. The research results show that M-banking has an influence on Sharia economics students' decisions on M-banking, where this is proven by the partial correlation results which show a significance value of 0.002<0.050.